Reconceptualising families in the EU: changes in demography, households and the allocation of care - DREW, EILEEN PATRICIA (Statistical and Social Inquiry Society of Ireland, 1997)
This paper charts the demographic changes characterising the last three decades, which have resulted in a diversity of family forms. It marks the magnitude of some of these changes, the exceptions to general patterns and how these may be combined to offer a new perspective on how we might view `families? and `households? in the EU. Macintyre states: Though sex, marriage, and reproduction may be linked empirically in a particular society and its dominant ideology.......We cannot assume a priori that people have babies because they are married, or marry in order to have babies; nor that people have babies because they have had sex, or that they have sex to produce babies (Macintyre 1991: 3).
Read before the Society, 8 May 1997
Keywords: Role of women; Family planning; Demographic change; Family structure; 314.15